2020
DOI: 10.1186/s12894-020-0584-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sarcomatoid differentiation and rhabdoid differentiation on prognosis for renal cell carcinoma with vena caval tumour thrombus treated surgically

Abstract: Background: Sarcomatoid differentiation in renal cell carcinoma (RCC) with vena caval tumour thrombus has been shown to be associated with aggressive behaviours and poor prognosis; however, evidence of the impact of rhabdoid differentiation on prognosis is lacking. This study evaluated the impact of sarcomatoid differentiation and rhabdoid differentiation on oncological outcomes for RCC with vena caval tumour thrombus treated surgically. Methods: We retrospectively analysed patients treated surgically for RCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Consistent with previous studies in our center, we found that the sarcomatoid feature is the independent predictor of poor prognosis in RCC and VTT treated surgically 19,20 . Abel et al 21 .…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies in our center, we found that the sarcomatoid feature is the independent predictor of poor prognosis in RCC and VTT treated surgically 19,20 . Abel et al 21 .…”
Section: Discussionsupporting
confidence: 91%
“…Rhabdoid differentiation in clear cell RCC has a typical pattern of dedifferentiation, suggesting poor prognosis, as reported by Yang et al [19]. Investigating the impact of rhabdoid and sarcomatoid differentiation on prognosis in 264 patients operated due to RCC, Kara et al reported that unlike sarcomatoid, rhabdoid differentiation was not associated with increased risk of lethality [20].…”
Section: Case Reportmentioning
confidence: 74%
“…In previous studies, blood indicators such as hemoglobin and neutrophils have been reported to be related to the prognosis ( 15 , 16 ). Sarcomatoid differentiation is currently considered a rare histologic variant that predicts aggressive behavior and poor prognosis ( 17 ). RCC with sarcomatoid differentiation is classified as grade 4 by the WHO/ISUP grading system ( 18 ).…”
Section: Discussionmentioning
confidence: 99%